Novel aminosilane (APTES)-grafted polyaniline@graphene oxide (PANI-GO) nanocomposite for electrochemical sensor - Alruwais, Raja Saad; Adeosun, Waheed A.; Marwani, Hadi M.; Jawaid, Mohammad; Asiri, Abdullah M.; Khan, Anish (MDPI, 2021)
Lead is a potentially toxic element (PTE) that has several adverse medical effects in humans. Its presence in the environment became prominent due to anthropogenic activities. The current study explores the use of newly developed composite materials (organic–inorganic hybrid) based on PANI-GO-APTES for electrochemical detection of Pb2+ in aqueous solution. The composite material (PANI-GO-APTES) was synthesized by chemical method and was characterized with SEM, XPS, XEDS, XRD, TGA, FTIR, EIS and CV. The result of characterization indicates the successful synthesis of the intended material. The PANI-GO-APTES was successfully applied for electrochemical detection of Pb2+ using cyclic voltammetry and linear sweep voltammetry method. The limit of detection of Pb2+ was 0.0053 µM in the linear range of 0.01 µM to 0.4 µM. The current response produced during the electrochemical reduction of Pb2+ catalyzed by PANI-GO-APTES was also very repeatable, reproducible and rapid. The application of PANI-GO-APTES-modified GCE in real sample analysis was also established. Therefore, PANI-GO-APTES is presented as a potential Pb2+ sensor for environmental and human health safety.